2021
DOI: 10.1093/ofid/ofab200
|View full text |Cite
|
Sign up to set email alerts
|

Lower Urine Tenofovir Concentrations Among Individuals Taking Tenofovir Alafenamide Versus Tenofovir Disoproxil Fumarate: Implications for Point-of-Care Testing

Abstract: From directly-observed-therapy studies, urine tenofovir (TFV) levels were 74% lower when taking tenofovir alafenamide (TAF) versus tenofovir disoproxil fumarate. Urine TFV remains quantifiable across a range of TAF adherence patterns, but a separate point-of-care lateral flow immunoassay with a lower TFV threshold will be needed to support TAF adherence monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…to indicate TDF or TAF adherence in other studies and was a less invasive method for assessing exposure in infants. 32,33 We found very low concentrations of TFV in infant urine with a median steadystate concentration of 5 ng/ml. We compared our findings to steadystate adult urine TFV concentrations reported in adults taking TDF and TAF, which were 12,504 and 1480 ng/mL, respectively.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…to indicate TDF or TAF adherence in other studies and was a less invasive method for assessing exposure in infants. 32,33 We found very low concentrations of TFV in infant urine with a median steadystate concentration of 5 ng/ml. We compared our findings to steadystate adult urine TFV concentrations reported in adults taking TDF and TAF, which were 12,504 and 1480 ng/mL, respectively.…”
Section: Discussionmentioning
confidence: 79%
“…To indirectly quantify infant drug exposure, we measured urine TFV concentrations. Measuring urine concentrations has been used to indicate TDF or TAF adherence in other studies and was a less invasive method for assessing exposure in infants 32,33 . We found very low concentrations of TFV in infant urine with a median steady‐state concentration of 5 ng/ml.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that therapeutic dose of TAF has a better renal safety profile compared with TDF, due to the fact that the level of TFV in the plasma is lower, hence lessens the exposure of proximal tubular epithelial cells to TFV [ 12 14 ]. However, TFV from TAF is still renally excreted and may cause tubular injury [ 15 – 17 ]. A pharmacokinetic study of a single-dose TAF administered to severe renal impairment participants with eGFR 15–29 mL/min/1.73m 2 resulted in higher TAF and TFV plasma levels compared to the matched normal healthy controls with eGFR ≥ 90 mL/min/1.73m 2 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recently tested LFA for tenofovir TDM in clinical specimens has the ULOQ of as high as 100 mg/L. 147 , 148 …”
Section: Carbapenem Dosingmentioning
confidence: 99%